Kategoria przestrzeni w studiach nad adaptacją. Reprezentacja społecznych peryferii w „Sąsiadach” (Adriana Markowskiego i Grzegorza Królikiewicza) - Birkholc, Robert (Zagadnienia Rodzajów Literackich, 2023)
The article is devoted to the category of space in adaptation studies. As the author argues, it is necessary to develop transdisciplinary tools that link formalistic and cultural approaches in comparative studies. The author proposes to use spatial properties such as center-periphery, internal-external, open-closed, as analytical tools in studies of space that can break the above divisions. As he argues, these notions should be treated in research not only as textual qualities, but also as conceptual frameworks triggering many different associations and discourses. The text that shows the benefits of using these analytical tools are Sąsiady, a collection of short stories by Adrian Markowski, and its film adaptation by Grzegorz Królikiewicz. Creating a representation of people from the social peripheries, the director makes significant changes in relation to the literary text. Królikiewicz tries to make a viewer take a different look at the social peripheries. Various formal experiments serve this purpose, above all the play with space, which is at the same time a play with social discourses. The author characterizes center-periphery, internal-external, open-closed relationships in both texts. He not only points out differences between literary and film text but shows how both media can think “about space” and think “through space.”